Processed data associated with the manuscript titled “Ice nucleating particle connections to regional Argentinian land surface emissions and weather during the Cloud, Aerosol, and Complex Terrain Interactions experiment” - DeMott, Paul (Colorado State University. Libraries, 2021)
By catalyzing primary ice nucleation of cloud droplets, ice nucleating particles (INPs) initiate the majority of precipitation. In addition, by modifying cloud optical properties they also impact radiative forcing. Here we present a multi-season study (October 2018 to April 2019) of INPs active via the immersion freezing mechanism during the Cloud, Aerosol, and Complex Terrain Interactions (CACTI) experiment, which took place in north central Argentina, a worldwide hotspot for mesoscale convective storms. The region has diverse potential natural INP sources, including native grassland and pasture, shrubland, pine plantation, low forest, and arable lands. INPs were measured untreated, after heating to 95 °C, and after hydrogen peroxide digestion, to identify biological (denatured by heat), other organic (decomposed by peroxide) and inorganic (remaining after peroxide digestion) INPs. No seasonal cycle of INP concentrations was observed. Biological INPs dominated the population active at -5 to -20 °C, while non-heat-labile organic INPs dominated at lower temperatures, from -20 to -28 °C. Inorganic INPs, presumably minerals, were minor contributors to the overall INP activity. Biological INP concentration active around -12 °C peaked during rain events and under high relative humidity (RH), reflecting emission mechanisms independent of the background aerosol concentration. The ratio of non-heat-labile organic:inorganic INPs was generally constant, suggesting they originated from the same source, presumably from regional arable topsoil based on air mass histories. Single particle mass spectrometry showed that soil particles aerosolized from a regionally-common agricultural topsoil contained known mineral INP sources (K-feldspar and illite) as well as a significant organic component. The INP activity observed in this study correlates well with agricultural soil INP activities from this and other regions of the world, suggesting that the observed INP spectra might be typical of many arable landscapes. These results demonstrate the strong influence of regional continental landscapes, emitting INPs of types that are not yet well represented in global models. It also highlights the value of differentiating these distinct types (biological, other organic, inorganic) and of resolving the influences upon their emissions through the use of a combination of immersion freezing methods, meteorological data, and aerosol characterization. Data will provide inputs for future parameterization development and numerical modeling studies of aerosol impacts on convective clouds and precipitation formation in the region.
Data assembled in this archive include raw and processed data appearing in figures for the noted publication, constituting data from the Cloud, Aerosol and Complex Terrain Interactions (CACTI) experiment, supported by the U.S. Department of Energy. These include merged total particle size distributions from 10 nm to 20 microns, the integrated surface areas from these total particle distributions, raw immersion freezing ice nucleating particle (INP) concentration data as a function of temperature for individual cases, “processed” INP concentration data for the same samples, and categorized INP concentration data for defined type of INPs that include biological, organic, and inorganic on the basis of the processed data. These categorizations are fully described in the publication. The total data coverage period is from October 3, 2018 to April 30, 2019. Baptiste Testa performed all calculations involving aerosol merging and INP particle typing. INP processing was performed by Thomas C. J. Hill, Kevin R. Barry, Carson C. Hume, and Hannah Hare.
Department of Atmospheric Science
Keywords: Atmospheric aerosols; Ice nucleating particles